Exploring the biomechanical characteristics of the weightlifting jerk - Lake, J.; Lauder, M.; Dyson, R. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The vertical ground reaction force (VGRF) and front foot sagittal plane movement of the weightlifting jerk were recorded from seven weightlifters. Average knee flexion during the dip phase was 58 ± 9 degrees (mean ± SD) at an average angular velocity of 125 ± 16 degrees.s-1 exerting a vertical impulse of 138 ± 17.3 Ns. The peak rate of force development was 17.2 ± 4.86 BW.s-1, the VGRF continuing to increase from a propulsion impulse of 113.7 ± 31.2 Ns to a peak drive phase value of 3.5 ± 1.2 BW, extending the knees by 54 ± 9 degrees. The front foot catch phase peak impact VGRF was 3.4 ± 1.2 BW loading at a rate of 285 ±119 BW.s-1. The results indicate that although loading rates are not excessive during the catch phase, careful consideration should be given before introducing the jerk into the strength and conditioning program of the inexperienced.